2005
DOI: 10.1002/fuce.200400082
|View full text |Cite
|
Sign up to set email alerts
|

Mastering Sulfonation of Aromatic Polysulfones: Crucial for Membranes for Fuel Cell Application

Abstract: The publication deals with the sulfonation of aromatic polysulfones that results in ionomers intended to be used as membranes for Proton Exchange Membrane Fuel Cells. The mechanical properties and the lifespan of the membranes depend, in particular, on the mode of synthesis of the ionomers and on chemical degradations which can occur and cut the polymeric chains. This article gives a progress report on the various methods giving access to polysulfone ionomers based on sulfonic acid functions. Among these metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
90
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(96 citation statements)
references
References 60 publications
1
90
0
5
Order By: Relevance
“…A wide range of characteriza tions was performed to determine the DS, indicating that NMR was the most accurate method. The Mn and PDI of the ionomers confi rmed that despite careful experimental conditions, CIS0 3 H produced signifi cant chain breakages, which were much more important than those induced by TMSCS, and consistent with the results reported by lojoiu et al [11 ]. Al though OS03H may appear more suitable for scaling up, we must emphasize that the expensive TMSCS can be easily generated in situ from a mixture of fairly cheap reagents (i.e., (CISi(CH 3 h) and CIS0 3 H).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…A wide range of characteriza tions was performed to determine the DS, indicating that NMR was the most accurate method. The Mn and PDI of the ionomers confi rmed that despite careful experimental conditions, CIS0 3 H produced signifi cant chain breakages, which were much more important than those induced by TMSCS, and consistent with the results reported by lojoiu et al [11 ]. Al though OS03H may appear more suitable for scaling up, we must emphasize that the expensive TMSCS can be easily generated in situ from a mixture of fairly cheap reagents (i.e., (CISi(CH 3 h) and CIS0 3 H).…”
Section: Discussionsupporting
confidence: 90%
“…The diphenylene sulfone endows the polymer backbone with insensi tivity to hydrogenation, thermal stability and oxidative resistance [10]. A comparative electrochemical study (i) of model molecules mimicking the backbone of high performance polymers and (ii) their sulfonated form confirmed that the polysulfone ionomers have a wider electrochemical stability window than that of polyether ether ketone and polyphenylene sulfide ionomers [11]. Therefore, sulfonated polysulfone (SPSU) ionomeric membranes have been extensively studied and tested for fuel cell applications [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai usaha telah dilakukan diantaranya pemakaian polimer alam (Mat and Liong, 2009;Ye et al, 2012), maupun sintetik (Smitha et al,2003;Iojoiu et al,2005. Polimer alam seperti kitosan dianggap cukup menjanjikan dalam aplikasi tersebut.…”
Section: Pendahuluanunclassified
“…Reaksi pembentukan basa schiff dengan beberapa modifikator telah dipublikasikan sebelumnya (Santos et al, 2005;Wiyarsi, 2008;Jiao et al,2011;Pramono et al, 2012 et al, 2000;Smitha et al, 2003;Iojoiu et al,2005). Material tersebut memilki stabilitas termal yang tinggi dan juga sifat mekaniknya yang cukup baik pula (Martins et al,2003), namun demikian modifikasi pada bahan tersebut perlu dilakukan agar menghasilkan material yang bermuatan, sehingga dapat digunakan sebagai membran penukar proton yang dapat diaplikasikan sebagai membran elektrolit.…”
Section: Pendahuluanunclassified
“…Activated carbon [5], carbon nano-tubes [6], sulfonated mesoporous silica [1], silica [7], and ironnickel oxide [8] are examples of inorganic materials that have been used as filler for the IEM matrix. The functions of inorganic fillers are to maintain water uptake, increase ion-exchange capacity and conductivity while retaining good mechanical and chemical stability [9]. However, the introduction of an inorganic filler into the polymer matrix should be carefully controlled to obtain a fine distribution of additives inside the membrane.…”
Section: Introductionmentioning
confidence: 99%